Shakespeare - Middleton, Haydn (Great Britain : ticktock Pub., 2003)
Offers a brief introduction to the life and times of playwright William Shakespeare, discussing his life in Stratford-upon-Avon, his career in London, the importance of the theatre in the time of Shakespeare, the influences behind his sonnets, and other related topics.
Includes index.
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Dramatists, English -- Early modern, 1500-1700.; Theater -- Great Britain -- History; English authors; English dramatists; Great Britain -- History -- Elizabeth, 1558-1603.; Great Britain -- Social life and customs -- 16th century; Great Britain -- History -- 1485-1603, Tudors; Great Britain -- Social life and customs